ANALISIS PERSEPSI PASIEN TERHADAP MUTU PELAYANAN PUSKESMAS DAN HUBUNGANNYA DENGAN KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS LEYANGAN KABUPATEN SEMARANG TAHUN 2018 - Aprina Hetikus Taekab; Chriswardani Suryawati; Wulan Kusumastuti (Jurnal Kesehatan Masyarakat (Undip), 2019)
Puskesmas as one of the first level health service units is a benchmark for health development and a proof of community participation. Not all puskesmas provide quality services that can give satisfaction to patients. Based on the results of the presurvey at the Semarang District Health Center Leyangan there were several problems that occurred. The research purpose was analyzing correlation of patient perceptions of the quality of service with satisfaction of outpatients at the Leyangan Health Center Semarang District in 2018. This research was a quantitative research with descriptive analytic research design and cross sectional approach. The research was located in the Semarang District Health Center Leyangan with a population of 5,438 patients with 100 respondents samples with data collection tools using questionnaires and analyzed by univariate and bivariate analysis with chi-square test. The results of univariate analysis show that in service quality, the respondents included in the good category are more than the pooZr respondents. The results of statistical tests using the chi-square test indicate that there is a relationship between service quality based on the dimensions of tangible (physical evidence) with patient satisfaction. There is a relationship between service quality based on the dimensions of reliability (reliability) with patient satisfaction. There is a relationship between service quality based on the dimension of responsiveness with patient satisfaction. There is a relationship between service quality based on the dimensions of empathy (empathy) with patient satisfaction. There is a relationship between service quality based on the assurance dimension with patient satisfaction. With each value = 0,000.